Li-chan: Forage factsheets - Bùi Văn Tùng; Phan Huy Chương; Trần Thị Bích Ngọc; Mai Thanh Tú; Atieno, Mary Otieno (2021)
Forage factsheets: How to grow, manage and utilize improved forages in the Northwest Highlands of Vietnam